EXPLORING THE INFLUENTIAL FACTORS AFFECTING EFFECTIVE IMPLEMENTATION OF PUBLIC PROJECTS IN ETHIOPIA: AN IN-DEPTH ANALYSIS - Abdi , Mohamed Ali; Hussein, Sara Ahmed (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study delves into the multifaceted landscape of public project implementation in Ethiopia, focusing on the specific case of Botor Tolay Woreda in the Oromia Regional State. Employing a mixed-method approach, combining quantitative and qualitative research methodologies, the research explores the intricate web of factors that influence the effective execution of public projects. The study draws upon the perspectives of 26 experienced individuals from government offices and contractor organizations, utilizing questionnaires, observations, and document analysis as primary data sources. Statistical analyses, including descriptive and inferential statistics, Pearson correlation, and multiple linear regression, are employed to establish relationships between independent variables such as planning and scope-related delays, client-related delays, contractor-related delays, and external factor-related delays, and the dependent variable of project implementation success. The findings underscore the significance of these factors in shaping the outcome of public projects. Notably, a positive and significant relationship is revealed between project implementation success and the aforementioned factors. The study provides valuable insights into the challenges faced in public project implementation in Ethiopia, shedding light on the critical role of effective planning, client engagement, contractor competence, and management of external factors. It is recommended that measures such as the establishment of construction oversight offices at the woreda level, improved payment approval processes, enhanced client collaboration, adherence to project schedules, and resilience against external influences be taken to mitigate delays and enhance project success.